2019
DOI: 10.1021/acs.jafc.9b03865
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Non-Targeted Method for Detecting the Adulteration of Black Pepper with a Broad Range of Endogenous and Exogenous Material at Economically Motivating Levels Using Micro-ATR-FT-MIR Imaging

Abstract: Infrared spectroscopy is often used as a simple, fast, and green method to screen for economically motivated adulteration in spices. However, conventional microscopy remains the reference method. In this research, the combination of microscopy and Fourier-transform infrared spectroscopy in mapping mode, namely, micro-FTIR imaging, along with Principle Component Analysis were used to develop a non-targeted method for detecting a broad range of organic and mineral bulking agents that could potentially be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The level of oleoresin removed from the spent material is also unknown, and this could affect the outcome of the result. It has also been reported that Bate's method cannot detect all forms of spent material, and therefore, investigation into other techniques was required [44]. Although some difficulties can be seen with spectroscopy, it does have some prospects as a first port of call for adulteration as a screening technique.…”
Section: External Validation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of oleoresin removed from the spent material is also unknown, and this could affect the outcome of the result. It has also been reported that Bate's method cannot detect all forms of spent material, and therefore, investigation into other techniques was required [44]. Although some difficulties can be seen with spectroscopy, it does have some prospects as a first port of call for adulteration as a screening technique.…”
Section: External Validation Resultsmentioning
confidence: 99%
“…Spent material has been detected in black pepper using non targeted methods at 10-30% [45] and ≥20% by Lafeuille et al [44]. Spent black pepper can be derived from light berries as they are used for oil extraction [44]. Light berries are berries without a seed/kernel [46] and are therefore different in nature from a typical black peppercorn.…”
Section: External Validation Resultsmentioning
confidence: 99%
“…Nondestructive methods based on infrared (IR) spectroscopy, including near-IR (NIR) and Fourier-transform-IR (FT-IR), have been applied to obtain black pepper fingerprints, and adulterated samples with different materials (e.g., cassava starch, chili powder, papaya seeds, talc, etc.) could be distinguished from authentic black pepper samples using PCA and OPLS-DA models. However, their low sensitivity related to the high signal-to-noise ratio , has led to the prevalent application of chromatographic techniques for food authentication purposes, including liquid chromatography (LC) and gas chromatography (GC) coupled to mass spectrometry (MS) . These analytical techniques allow the separation of a large number of metabolites which may be subsequently identified using databases or by reference standard analysis …”
Section: Introductionmentioning
confidence: 99%
“…Thus, various aspects of quality control of this product are vital to the sustainability of its market [28][29][30][31] . A prominent example is the development of analytical methods 32,33 to detect adulteration by cheaper materials, e.g., pepper husk or papaya seed. Perhaps another important aspect of the quality control is geographical indication, which has become an increasingly important leveraging tool in trade negotiations 34,35 and sales valuation of products.…”
Section: Introductionmentioning
confidence: 99%